A single layer negative index meta atom at microwave frequencies. Issue 6 (30th March 2017) - Hasan, M.M.; Faruque, M.R.I.; Islam, M.T.
ABSTRACT: A single layer negative index meta atom is described that is developed by an outer and inner split ring resonators with inverse E‐shape metal strips of copper are connected with the outer ring resonator that look like a mirror‐shape structure. Finite integration technique based CST Microwave Studio is utilized to design, simulation and analysis purposes, where the Agilent N5227A vector network analyzer is used for measurement. Measurements shows that, the measured and simulated performances are well complied together. This design illustrates 5.81 GHz wide bandwidth and applicable for tri (C‐, X‐ and Ku‐) band applications. The total dimensions of the designed structure are 0.2λ × 0.2λ × 0.035λ and the effective medium ratio 5 makes the proposed biaxial meta atom is suitable for practical applications. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1450–1454, 2017